Importance of program physical activity in quality of life in multiple sclerosis patients, six months after the intervention - Pedro, Luísa (2015)
Background: Multiple Sclerosis (MS) is a chronic disease of the central nervous system that affects more often young adults in the prime of his career and personal development, with no cure and unknown causes. The most common signs and symptoms are fatigue, muscle weakness, changes in sensation, ataxia, changes in balance, gait difficulties, memory difficulties, cognitive impairment and difficulties in problem solving MS is a relatively common neurological disorder in which various impairments and disabilities impact strongly on function and daily life activities. Purpose: The aim of this study is to examine the implications of an Intervention Program of Physical Activity (IPPA) in quality of life in MS patients, six months after the intervention.